REVIVE a surveillance programme for ticks and tick-borne diseases: molecular detection of B. burgdorferi s.l. and Rickettsia spp. - Lopes de Carvalho, I. (2014)
Objectives: To assess the risk posed by ticks and tick-borne pathogens to Public Health is essential to have reliable data on tick population, namely main species, status, distribution and the changing trends in tick distribution and abundance. Since 2011 the Ministry of Health requested the National Institute of Health to implement and coordinate a national surveillance programme for ticks and tick-borne diseases. Methods: During 2012 and 2013, ticks were collected from hosts and on the vegetation by flagging method. Results: Through the engagement of several health agencies, more than > 18 000 ticks from 119 municipalities across mainland Portugal have been submitted, representing 13 tick species Dermacentor marginatus; D. reticulatus; Haemaphysalis punctata; Hyalomma lusitanicum; H. marginatum; Ixodes canisuga; I. hexagonus; I. ricinus; I. ventalloi; Rhipicephalus annulatus; R. bursa; R. pusillus and R. sanguineus. The majority of ticks sent to the laboratory were R. sanguineus (69%), followed by R. pusillus (16.4%) and H. marginatum (9.7%). The other tick species were collected in occasionally, such as I. ricinus with only 0.3%. Two hundred and thirty three ticks were collected on humans and R. sanguineus was the most frequent (41%) followed by I. ricinus (20%). All the human ticks and about 5% of the ticks collected from vegetation or in hosts were analyzed for the presence of Borrelia spp and Rickettsia spp. B. lusitaniae and seven rickettsial species were detected, R. aeschlimannii, R. conorii Malish, R. helvetica, R. massilae, R. raoulti and R. slovaca. Some ticks species was found only infected with a bacterial agent, as for example H. marginatum with R. aeschlimannii, and D. reticulatus with R. slovaca, when others as R. sanguineus and I. ricinus were infected with three different agents (R. conorii Malish, R. massilae and B. lusitaniae and R. helvetica, R. monacensis, B. lusitaniae, respectively). Due to the high density of Hyalomma spp. present in Portugal and the recent detection of crimean congo hemorrhagic fever virus (CCHF) in Spain, the surveillance of this virus is being implemented during this year. Conclusions: REVIVE program has already produced valuable results and will be maintained for at least the next three years that will allow to observe the trends in the Portuguese tick fauna and pathogens. Another important output of this network is to raise awareness about tick-borne diseases among the populations and the healthcare providers as medical doctors and nurses. Keywords: surveillance programme, ticks, tick-borne diseases